2021
DOI: 10.3390/su13126528
|View full text |Cite
|
Sign up to set email alerts
|

Applying Talent Quality-Management System (TTQS) to Enhance Information Literacy, Learning Motivation, and Computational Thinking Competency of Nursing Undergraduates

Abstract: In Taiwan, the Ministry of Education started promoting computational thinking (CT) and design skills in the programming curriculum in 2018 at all universities. CT, which has been widely discussed in the field of education, is the ability to solve problems that use computer science concepts. For students in non-information technology fields, such as nursing students, a curriculum that integrates nursing education and information literacy can bolster evidence-based practice, enhance professional development, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…A positive correlation was found between the collaboration concept analysis and nurse leader collaboration (r = 4.33 p < .01); furthermore, the interprofessional collaboration was positively correlated with professional students' collaboration education (r = 0.59 p < .01) For example, a study by Bahrami et al (2018) on gerontological nursing adopted semi-structured interviews among 25 participants (9 nurses, 12 nurse managers, 4 clinical instructors) and demonstrated emotional competence in caring for older people including a positive attitude, creativity in care, successful relationship management and compassionate care in practice nursing for older people. Research on computational thinking is extremely rare, with only one study (Wu et al, 2021), which applied a talent quality-management system to enhance nursing students' computational thinking competency. Computational thinking has been narrowly discussed in the training arena.…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation was found between the collaboration concept analysis and nurse leader collaboration (r = 4.33 p < .01); furthermore, the interprofessional collaboration was positively correlated with professional students' collaboration education (r = 0.59 p < .01) For example, a study by Bahrami et al (2018) on gerontological nursing adopted semi-structured interviews among 25 participants (9 nurses, 12 nurse managers, 4 clinical instructors) and demonstrated emotional competence in caring for older people including a positive attitude, creativity in care, successful relationship management and compassionate care in practice nursing for older people. Research on computational thinking is extremely rare, with only one study (Wu et al, 2021), which applied a talent quality-management system to enhance nursing students' computational thinking competency. Computational thinking has been narrowly discussed in the training arena.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that the usefulness of the web portal would affect students' satisfaction. Wu et al. (2021) found that perceived course usefulness would influence nursing undergraduate students' learning attitudes and outcomes in a computer programming course.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Talent echelon construction, as an important project affecting enterprise human resource management, should be by the company's senior management, department heads and other relevant personnel in charge of the attention and concern [2]. And actively take various supporting measures to steadily promote the implementation of the talent echelon construction work, and effectively bring into play the advantageous effect of the talent echelon construction work [3][4].…”
Section: Introductionmentioning
confidence: 99%